The Kinesin Superfamily Handbook Transporter, Creator, Destroyer - Friel, Claire T. (Taylor & Francis, 2020)
This book brings together current information on the families that make up the kinesin superfamily of molecular motors in one comprehensive text. It is an ideal reference for researchers looking to make comparisons between different families, for specific information on an individual family, or simply for an overview of the kinesin superfamily. Information is clearly structured and grouped according to individual families and organiszed in a standardiszed way, allowing the reader to easily search and retrieve information on this large superfamily of molecular motors and understand how its individual members carry out a diverse variety of cellular functions. Features: The first book dedicated to the entire kinesin superfamily. Enables a fuller understanding of this family of proteins, which is becoming an increasing focus of research due to its involvement in diseases such as cancer, neuropathies and ciliopathies. Written in a manner accessible to a range of researchers in life and medical sciences, including biophysicists, biochemists, and medical researchers.